Financial and non-financial performance measurement system on managerial performance through prosedural fairness and trust in superiors in manufacturing companies in Indonesia - Anton Arisman; Kathryn Sugara; Yulizar Kasih; Usniawati Usniawati (INOVASI, 2022)
The purpose of this study is to investigate the effect of Financial and Non-Financial Performance Measurement System on Managerial Performance through Prosedural fairness and Trust in Superiors in Manufacturing Companies in Indonesia   The data used in this study is primary data with a sample about 153 respondents. The results of this study indicate the financial performance measurement system and non-financial performance measurement system have a positive affect on procedural fairness. However,  financial performance measurement system does not affect on trust in superior. The financial performance measurement system also does not significantly affect on trust in superior. However, non-financial performance measurement system has effect on trust in superior. The financial performance measurement system and non-financial performance measurement system have a positive effect on managerial performance. The limitation of this study has low R2 and doing the survey. The suggestion for future research can more investigate with other variables such as role clarity, role conflict, interpersonal trust and psychological empowerment.  The last suggestion for future research is the qualitative method in their research, such as interview and case study.